United European Gastroenterology Week scientific abstracts and their progression to full publication. Issue 10 (October 2017) - Raju, Suneil A.; Sanders, David S.; Akram, Rahim; Glover, Rebecca; Al-Rifaie, Ammar; Peever, Elise; Purves, Josh; Scanu, Emily; Kurien, Matthew
Abstract : Objective: Abstracts presentations at scientific meetings enable rapid dissemination of novel research. The percentage of abstracts that proceed to full publication from differing medical specialties is highly variable. This study aims to evaluate the outcomes of abstracts presented at the United European Gastroenterology Week (UEGW). Materials and methods: All abstracts presented at UEGW between 2009 and 2011 were assessed. Cross-referencing of the first author, senior author and at least one keyword of the abstract was performed using PubMed and EMBASE databases. Abstracts and possible resultant full publications were then examined in tandem to ensure that they represented the same study. Data were also collected on lag time to publication, journal impact factors, country of the author and factors influencing subsequent publication. Results: A total of 6785 abstracts (1438 oral and 5347 poster presentations) were presented during the period assessed. Of these, 2099 (30.9%) proceeded to full publication in indexed journals. Oral abstract presentations were most likely to proceed to full publication compared with poster presentations (odds ratio: 1.38, 95% confidence interval: 1.22–1.56) and were more likely to achieve publication in higher impact journals (median impact factor 4.78 vs. 2.89, P <0.0005). The median lag time to full publication was 15 (IQR: 7–15) months. The Netherlands had the highest United European Gastroenterology abstract conversion rate to full publication (46.8%). Conclusion: This is the first study to assess the publication rates of UEGW. Findings are favourable with similar studies from other societies.